Design of a Digital Service Information System for Web-Based Wedding Management Invitation System - Huda, Alamul; Handrianto, Yopi (Information Technology and Systems, 2025)
The Digital Wedding Invitation Management System provides a modern solution for efficiently managing wedding invitations in digital format. This research is driven by the increasing need for a platform that allows couples to create, manage, and distribute wedding invitations online, in response to contemporary lifestyle changes and the complexities involved in organizing weddings today. This system aims to simplify the invitation process by offering tools that allow couples to personalize and share invitations while enhancing interaction with guests through digital communication features. Developed using Agile methodology, this system benefits from iterative development and continuous user feedback, ensuring that it meets the evolving needs. This system is built on the Laravel framework, known for its scalability and reliability, ensuring a secure and high-performance platform. This research includes various stages, including needs analysis, system design, implementation, and thorough testing to ensure the reliability and quality of the system. The result is a user-friendly and efficient Digital Wedding Invitation Management System, which helps couples manage their wedding invitations easily, reducing the time, effort, and costs typically associated with traditional invitations. This system represents an innovative approach to digital invitation management, providing greater convenience and accessibility for users throughout the wedding planning process.